The Most Dominant Predictability Factor of Boey Score on The Level of Mortality in Perforation Gaster Boey Score 1 and Boey Scores 2 Patients in RSUD Dr Soetomo Surabaya - Sandi Halim Naga Saputra; Vicky Sumarki Budipramana; Marjono Dwi Wibowo (HM Publisher, 2021)
Introduction: The Boey score is the most commonly used scoring system for risk stratification because of its simplicity and high predictive value for mortality and morbidity in cases of gastric perforation. This score is widely used in daily practice because it only assesses 3 assessment components; namely the onset of perforation, shock at first admission, and comorbid disease; which is easy to do and has a fairly good accuracy. In Boey score 2, the mortality rate is still high, so research on the factors that most influence mortality at Boey Score 2 needs to be done.Methods: This study uses secondary data from medical records of patients who meet criteria of inclusion and exclusion. This study is a comparative test using a cohort analytic observational study design (longitudinal retrospective), comparing the components of the Boey score which is the most influential in predicting the mortality rate in gastric perforated patients. Boey score 1 and Boey score 2 at RSUD Dr. Soetomo SurabayaResults: Total subject of the study was 65 people, consisting of 43 men (66.2%) and 22 women (33.8%). The Boey score was 16 people (24.6%) with a Boey score of 1 and 49 people (75.4%) with a Boey score 2.From the Boey score component, 49 people (75.4%) were obtained with the onset of perforation> 24 hours, 31 people (47.7%) with preoperative shock, and 34 people (52.3%) with comorbidities. Comorbidity in study subjects included hypertension in 17 people (26.2%), diabetes mellitus in 4 people (6.2%), heart disease in 4 people (6.2%), lung disease in 5 people (7.7%), and kidney disease in 7 people. people (10.8%)Conclusion: Shock is the most dominant Boey Score predictability factor that affects the mortality rate in gastric perforation patients with Boey score 1 and Boey score 2.